2022
DOI: 10.1515/biol-2022-0060
|View full text |Cite
|
Sign up to set email alerts
|

Alleviative effects of magnetic Fe3O4 nanoparticles on the physiological toxicity of 3-nitrophenol to rice (Oryza sativa L.) seedlings

Abstract: In the present study, we explored whether magnetic iron oxide nanoparticles (MNPs-Fe3O4) can be used to alleviate the toxicity of 3-nitrophenol (3-NP) to rice (Oryza sativa L.) seedlings grown under hydroponic conditions. The results showed that 3-NP from 7 to 560 μM decreased the growth, photochemical activity of the photosystem II (PS II), and chlorophyll content of the seedlings in a concentration-dependent manner. In the presence of 3-NP, 2,000 mg L−1 MNPs-Fe3O4 were added to the growth medium as the absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Moreover, Li et al also found that low doses of zero-valent iron (ZVI) and Fe 3 O 4 NPs could be used as an alternative to Fe fertilizers and improve plant growth under Fe-deficient conditions by alleviating oxidative stress and regulating phytohormones in rice plants caused by Fe deficiency [ 23 ]. In addition, Sainao et al used MNPs-Fe 3 O 4 (iron oxide nanoparticles containing both Fe 2+ and Fe 3+ ions) to mitigate the toxic effects of 3-nitrophenol on rice seedlings [ 27 , 28 , 29 ].…”
Section: Effect Of Monps On the Growth Of Ricementioning
confidence: 99%
“…Moreover, Li et al also found that low doses of zero-valent iron (ZVI) and Fe 3 O 4 NPs could be used as an alternative to Fe fertilizers and improve plant growth under Fe-deficient conditions by alleviating oxidative stress and regulating phytohormones in rice plants caused by Fe deficiency [ 23 ]. In addition, Sainao et al used MNPs-Fe 3 O 4 (iron oxide nanoparticles containing both Fe 2+ and Fe 3+ ions) to mitigate the toxic effects of 3-nitrophenol on rice seedlings [ 27 , 28 , 29 ].…”
Section: Effect Of Monps On the Growth Of Ricementioning
confidence: 99%
“…Furthermore, as MWCNTs are rich in oxygenated functional groups that face outward, they can easily and efficiently crosslink with β-CD through acetalization [38]. The addition of CNTs onto the hydrogel structure was expected to overcome the collapsing and high solubility problems caused by the weakening of electron repulsion and the reduction of oxygenated functional groups during the sorption process [38,39]. In addition, the concentration of the Ni(II) solution after and before adsorption was used to study the change in Ni(II) concentration in the solution.…”
Section: The Novel Aspect Of This Workmentioning
confidence: 99%
“…pected to overcome the collapsing and high solubility problems caused by the weakening of electron repulsion and the reduction of oxygenated functional groups during the sorption process [38,39]. In addition, the concentration of the Ni(II) solution after and before adsorption was used to study the change in Ni (II) concentration in the solution.…”
Section: The Novel Aspect Of This Workmentioning
confidence: 99%